KEKERASAN DALAM RUMAH TANGGA MUDA DI DESA MANUMPITAENG KABUPATEN SANGIHE - Kesia Angreani Karame; Maryam Lamadirisi; Zoni Henki Singal (Labor Program Studi Pendidikan Sosiologi, 2021)
The purpose of this study is to find out the Young Domestic Violence in Manumpitaeng Village, Sangihe Regency. This research uses qualitative research, with techniques in the form of interviews and observations, data validation in this study using internal validation of external validation, reliability and objectivity, Sugiyono 2010. The results showed that the violence that occured in the young household in Manumpitaeng village was due to easy marriage, was pregnant first and had stopped school. Economic factors, insufficient salaries to meet the needs of households every month often cause quarrels. And it can be described that the parents of the husband or wife always interfere in their child’s household such as finansial problems, child education, work, moreover this can be triggered because of differences in attitudes towards each parent.